Seamus Heaney and the Politics of Tragedy: Navigating Trauma and Moral Dilemmas in The Cure at Troy and The Burial at Thebes - Jaber, Soltan (FOCUS: Papers in English Literary and Cultural Studies, 2025)
This paper examines how institutional contexts, both theatrical and political, influence the production and reception of Seamus Heaney’s The Cure at Troy (1990) and The Burial at Thebes (2004), versions of Sophocles’ Philoctetes and Antigone, respectively. Heaney, known for actively participating in Dublin protests to support global equality and for visiting South Africa during the apartheid years, wrote The Cure at Troy during the later years of the Northern Irish Troubles, long before any formal peace process had materialized, thereby embedding Irish political and social realities within the play’s ethical fabric. The play became part of the broader institutional framework addressing the Troubles, as its performances often occurred in the shadow of political turmoil, shaping the audience’s outlook. Similarly, The Burial at Thebes comments on the military and political forces of Unionist and Nationalist organizations during and following the Troubles, using theatre to navigate the ethical dilemmas of patriotism, familial obligation, and honoring the deceased. The plays’ performance history, especially in institutional contexts such as the Abbey Theatre in Dublin, demonstrates the impact of cultural production on political institutions and vice versa. The interplay between tragedy and institutional issues is further emphasized by the political suggestions in Sophocles’ Philoctetes, which reflect Alcibiades’ resurgence—a Greek general expected to return from exile to offer military guidance during the Second Peloponnesian War. In this respect, Heaney’s drama mirrors Sophocles’ work, as both authors engage with their respective political landscapes through performance.